Critical Analysis Of Law No. 30 Of 1999 On Arbitration And Alternative Dispute Resolution Related To The Potential Development And Implementation Of Online Arbitration - Wisnu Tikoariaji (Green Publisher Indonesia, 2024)
This paper critically examines the relevance of Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution in the context of online arbitration. With the rapid growth of e-commerce and the increasing reliance on technology for dispute resolution, the legal framework governing arbitration in Indonesia has become outdated. While various arbitration institutions, such as BANI and the ICC, have adopted online arbitration processes, the existing legislation fails to accommodate these developments. This research highlights the potential legal uncertainties that arise from the lack of provisions for online arbitration in the current law and underscores the need for immediate legislative revisions. By analyzing relevant legal norms and the implementation of electronic arbitration regulations, the study aims to provide insights into how the law can be modernized to better serve the needs of contemporary dispute resolution practices in the digital age.